2021
DOI: 10.1063/5.0044713
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic viral inactivation: Recent advances and potential applications

Abstract: Antibiotic-resistant bacteria, which are growing at a frightening rate worldwide, has put the world on a long-standing alert. The COVID-19 health crisis reinforced the pressing need to address a fast-developing pandemic. To mitigate these health emergencies and prevent economic collapse, cheap, practical, and easily applicable infection control techniques are essential worldwide. Application of light in the form of photodynamic action on microorganisms and viruses has been growing and is now successfully appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 155 publications
0
23
0
1
Order By: Relevance
“…In contrast, new chemicals and materials can wonderfully assist the rapid detection and preliminary screening of such pathogens. For example, we can develop new chemical reagents, novel materials, and clinical diagnostic kits for infectious diseases such as COVID-19, viral hepatitis, tuberculosis, AIDS, hemorrhagic fever, dengue fever, influenza, and diarrhea; we could also design high-throughput diagnostic chemical reagents or materials and supporting equipment accordingly that can simultaneously detect multiple pathogens and discrepancy in drug resistance [20] , [37] ; chemically modified environmental-friendly metals like copper or silver nanoparticles, and even polymer-metal nanocomposites could be prepared for antibacterial or antiviral applications in sterilization [26] , [38] , [39] , [40] ; novel chemical formulations, materials, sprays, gels, and other relevant products with photo [41] , [42] , [43] , sound, magnetic [44] , [45] and thermal responsiveness might be developed; specifically designed disinfectants and biosafety cleaning systems could be applied for the open environment as well as confined space especially with personnel on-site.…”
Section: Possible Application Of Biosafety Chemistry and Biosafety Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, new chemicals and materials can wonderfully assist the rapid detection and preliminary screening of such pathogens. For example, we can develop new chemical reagents, novel materials, and clinical diagnostic kits for infectious diseases such as COVID-19, viral hepatitis, tuberculosis, AIDS, hemorrhagic fever, dengue fever, influenza, and diarrhea; we could also design high-throughput diagnostic chemical reagents or materials and supporting equipment accordingly that can simultaneously detect multiple pathogens and discrepancy in drug resistance [20] , [37] ; chemically modified environmental-friendly metals like copper or silver nanoparticles, and even polymer-metal nanocomposites could be prepared for antibacterial or antiviral applications in sterilization [26] , [38] , [39] , [40] ; novel chemical formulations, materials, sprays, gels, and other relevant products with photo [41] , [42] , [43] , sound, magnetic [44] , [45] and thermal responsiveness might be developed; specifically designed disinfectants and biosafety cleaning systems could be applied for the open environment as well as confined space especially with personnel on-site.…”
Section: Possible Application Of Biosafety Chemistry and Biosafety Materialsmentioning
confidence: 99%
“…[49] . In short, it is imperative to apply new chemical subtances and materials to develop light, electric, sound, magnetic, and thermo-responsive disinfectants that are colorless, odorless, non-toxic, non-corrosive, environment-friendly, and degradable with no heavy metal residuals [41] , [42] , [43] .…”
Section: Possible Application Of Biosafety Chemistry and Biosafety Materialsmentioning
confidence: 99%
“…A considerable number of in vitro studies regarding photoinactivation of viruses have been performed, and have already been reviewed by several authors [ 80 , 81 , 268 271 ]. It was found that photoinactivation of viruses possessing a lipid envelope, like the one presented in Fig.…”
Section: Virusesmentioning
confidence: 99%
“…As an active method to kill microbes on device surfaces, the ETT can be coated with various antiseptic substances to prevent VAP. Examples of such antiseptic substances include silver nanoparticles (AgNPs) [ 14 , 15 ], silver sulfadiazine/chlorhexidine [ 16 ], zinc oxide [ 17 ], antimicrobial peptide [ 18 ], and photodynamic therapy [ 19 , 20 ] wherein the incorporation of these substances into surface coatings has been found to minimize biofilm formation and bacterial growth. In addition, some passive methods to deal with microbial adhesion have been applied to ETTs to produce a contamination-resistant surface by altering the surface composition and pattern.…”
Section: Introductionmentioning
confidence: 99%